Kolaborasi Pemerintah dan Masyarakat Dalam Pengembangan Obyek Wisata Tanjung Malaha Kabupaten Kolaka - abdul sabaruddin; Adnan, Robin; Maulid, Maulid (Program Pasca Sarjana Universitas Garut, 2024)
Tourism is an important sector that has a role in driving economic growth and regional development. The tourism sector plays a role in increasing regional income and community welfare. To optimize this potential, the collaborative government and community are the primary keys in the development of tourism objects. This research is qualitative descriptive research with data collection carried out through interview and documentation techniques. Research informants used purposive sampling techniques. The results of the interviews and documentation were then analyzed using interactive methods which included data condensation, data presentation and drawing conclusions. The research results show that in developing the Tanjung Malaha tourist attraction, communication is an important aspect of collaboration because open communication can provide access to information regarding needs in developing the tourist attraction. However, this aspect is still less effective so it has an impact on the level of community participation in deliberation activities for the development of tourist attractions. This condition also causes differences in views among tourism awareness groups (Pokdarwis) regarding understanding the management of tourist attractions.